Gynaecotyla squatarolae (Digenea: Microphallidae) from rats experimentally infected with metacercariae from the shore crab, Macrophthalmus dilatatus - Seo, Min (The Korean Society for Parasitology, 2007)
Metacercariae of Gynaecotyla squatarolae (Digenea: Microphallidae) were discovered from the shore crab, Macrophthalmus dilatatus, purchased at a market in a coastal town of Taean-Eup, Chungcheongnam-do, Republic of Korea. Their adult flukes were confirmed by experimental infection of rats. The metacercariae of G. squatarolae were elliptical (391.1 x 362.5 µm), and the excysted metacercariae had progenetic genital organs, including the ovary and testes. To obtain adult flukes, 6 Sprague-Dawley rats were fed 500 metacercariae each, and killed at days 2, 4, and 6 post-infection. The adult flukes were identified as G. squatarolae (Yamaguti, 1934) Yamaguti, 1939, based on morphological characters, including 2 ventral suckers (1 large and 1 small), a large genital atrium equipped with the cirrus and the metraterm, separated male and female genital pores, a transversely long cirrus pouch, and extensive vitelline follicles. In the present study, it has been first proven that the shore crab M. dilatatus is a second intermediate host for G. squatarolae in the Republic of Korea.